Restauração florestal através de semeadura direta de duas espécies nativas - Hüller, Alexandre (2011)
The forest restoration in the Atlantic Forest Biome is still a great challenge. The direct sowing of native species may be a viable alternative, especially for small farms. The aim of this project was to evaluate the germinative potential of two native species from Rio Grande do Sul, Brazil (Schinus terebinthifolius Raddi and Citharexylum solanaceum Chamisso) under laboratory, vivarium and field conditions, through direct sowing. The analysis of germination in laboratory and vivarium were held at the Regional University of the Northwest State of Rio Grande do Sul, Municipality of Ijuí/RS, Brazil, in the period of September-October of 2009. For the species C. solanaceum, was also held an additional treatment with mechanically scarified seeds. As for the direct sowing, it was used 50 seeds in each parcel, with six different treatments for each species (T1 witness without seeds; T2 - burial of seeds; T3 - burial of seeds with leaf litter; T4 - burial of seeds with soil buch; T5 - burial of seeds with leaf litter and soil bush); T6 witness with soil bush and leaf litter without seeds, evaluating germination and initial survival. The conventional tillage by forest seedlings had two treatments (T1 - S. terebinthifolius and T2 - C. solanaceum). In laboratory, germination had a significant difference for S. terebentifolius with 49.6% in relation to C. solanaceum, which showed 5.6% and 9.2% for normal and scarified seeds, respectively. Now, in vivarium, S. terebinthifolius presented (49.6%) of germination and C. solanaceum (10% and 43.2%) for normal and scarified seeds, respectively. For direct sowing in the field, the specie S. terebinthifolius showed a significant difference in the percentage of initial survival for the treatment T5, on 30 and 360 days, respectively, compared to other treatments. The specie C. solanaceum did not germinate in field. For the initial growth, the treatment also showed results statistically superior to the other ones, with 42cm height on 360 days after sowing. In conventional tillage S. terebinthifolius showed 84.33% of survival and 88,46 cm height while C. solanaceum reached 92% of survival and 77,51 cm height after one year. The costs for the implantation and maintenance of the different treatments of direct sowing, when added leaf litter and soil bush, presented higher values than the conventional tillage.